Metatalk Moves: Examining Tools for Collective Academic Discourse Learning. (14th October 2020) - Phillips Galloway, Emily; McClain, Janna B.
Abstract: Educators are increasingly aware of the role of classroom talk in cultivating students' language knowledge, which in turn supports their skilled reading comprehension. The result has been greater attention to teacher talk moves that transform class discussions into opportunities for language learning. However, less focus has been placed on the strategies used by students as they work together to both learn language and learn about language. The authors focus on a fourth‐grade classroom in which students scaffold one another's language development through powerful language‐focused talk, or metatalk, during a small‐group vocabulary activity. By examining the characteristics of these metatalk episodes and delineating talk moves used by students within them, the authors make visible moves that educators might note and build from. This study informs instruction that capitalizes on the language knowledge held by individual learners in the service of collective language learning for all.